The absolute chronology of the funeral bags of the Chancay culture of the Cerro Colorado cemetery, Huacho - Dalen Luna, Pieter van (2021)
This study presents the report of the chemical and archeometric investigations carried out in a set of samples recovered from the mummies of Cerro Colorado, a funerary area located at the southern end of the Huaura valley. North-central coast of Peru. The results show us that it was during the late Intermediate Period (Chancay culture) when burials intensified in this important funeral area, the largest on the Peruvian coast. Apparently, the use of resources for the elaboration of more elaborate textiles would be related to a period of optimun climaticum, in which living standards were considerably improved, especially in coastal societies.